Analisis Risiko Produksi dan Pendapatan Pertanian Padi di Desa Harapan Kabupaten Boalemo - Hestina Dewinta Sari; St. Aisyah R St. Aisyah R; Karlena Arsyad (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
Lowland rice is crucial in ensuring a stable food supply in a region. Uncertainty in harvest yields and farmers' income can disrupt food distribution, ultimately impacting food security in the area. This study examines the production and income risks associated with lowland rice farming in Harapan Village. The study was conducted from May to July 2024, utilizing data from a single planting season. The population involved in this study consisted of 424 farmers, and samples were selected using a simple random technique, with calculations based on the Slovin formula. This resulted in a sample of 40 farmers, with a margin of error of 15%. Data were collected through direct interviews (primary data) and secondary data from related agencies. The variables analyzed include fixed and variable costs, income calculated from revenue and expenditure, and risk measured by average production, standard deviation, and coefficient of variation. The data were analyzed descriptively and quantitatively using Microsoft Excel 2021 to evaluate fluctuations in production and income. The results of the study indicate that the low level of production risk, as reflected in the Coefficient of Variation (CV) value of 0.50, suggests that rice farming in Harapan Village is relatively stable and not significantly affected by large fluctuations. However, even though the production risk is relatively low, farmers' income, which averages IDR 14,110,668 per planting season, is still limited because most of the income is used to cover production costs and debt obligations, which ultimately affects farmers' ability to obtain greater profits.